Nonrelativistic Quantum Mechanical Problem for the Cornell Potential in Lobachevsky Space - Laszlo Jenkovszky; Yurii Andreevich Kurochkin; N. D. Shaikovskaya; Vladimir Olegovich Soloviev (Universe, 2024)
In Friedmann–Lobachevsky space-time with a radius of curvature slowly varying over time, we study numerically the problem of motion of a particle moving in the Cornell potential. The mass of the particle is taken to be a reduced mass of the charmonium system. In contrast to the similar problem in flat space, in Lobachevsky space the Cornell potential has a finite depth and, as a consequence, the number of bound states of the system is finite and motion with a continuum energy spectrum is also possible. In this paper, we study the bound states as well as the scattering states of the system.